Transcriptome sequencing reveals genome-wide variation in molecular evolutionary rate among ferns. (December 2016) - Grusz, Amanda; Rothfels, Carl; Schuettpelz, Eric
Abstract Background Transcriptomics in non-model plant systems has recently reached a point where the examination of nuclear genome-wide patterns in understudied groups is an achievable reality. This progress is especially notable in evolutionary studies of ferns, for which molecular resources to date have been derived primarily from the plastid genome. Here, we utilize transcriptome data in the first genome-wide comparative study of molecular evolutionary rate in ferns. We focus on the ecologically diverse family Pteridaceae, which comprises about 10 % of fern diversity and includes the enigmatic vittarioid ferns—an epiphytic, tropical lineage known for dramatically reduced morphologies and radically elongated phylogenetic branch lengths. Using expressed sequence data for 2091 loci, we perform pairwise comparisons of molecular evolutionary rate among 12 species spanning the three largest clades in the family and ask whether previously documented heterogeneity in plastid substitution rates is reflected in their nuclear genomes. We then inquire whether variation in evolutionary rate is being shaped by genes belonging to specific functional categories and test for differential patterns of selection. Results We find significant, genome-wide differences in evolutionary rate for vittarioid ferns relative to all other lineages within the Pteridaceae, but we recover few significant correlations between faster/slower vittarioid loci and known functional gene categories. We demonstrate that the faster rates characteristic of the vittarioid ferns are likely not driven by positive selection, nor are they unique to any particular type of nucleotide substitution. Conclusions Our results reinforce recently reviewed mechanisms hypothesized to shape molecular evolutionary rates in vittarioid ferns and provide novel insight into substitution rate variation both within and among fern nuclear genomes.